ABO blood type compatibility is not a risk factor for gestational trophoblastic neoplasia development from androgenetic complete hydatidiform moles. (8th April 2020) - Sato, Asuka; Usui, Hirokazu; Shozu, Makio
Abstract: Problem: Complete hydatidiform moles (CHMs) are allografts to patients in terms of an androgenetic origin. Thus, some immunological reactions may be involved in the development of gestational trophoblastic neoplasia (GTN) from CHMs. This study aimed to evaluate the effect of ABO blood group on the prognosis of androgenetic CHMs. Method of Study: A total of 129 patients who were diagnosed as having CHMs based on multiplex short tandem repeat polymorphism analysis were included. The ABO blood types of molar tissues were determined by single‐nucleotide polymorphisms in the ABO gene using a high‐resolution melting assay. The incidence of GTN was compared based on ABO compatibility between the patients and their molar tissues. Results: The overall incidence of GTN was 17.1% (22/129). Gestational trophoblastic neoplasia occurred in 10.8% (4/37), 14.8% (8/54), 22.2% (6/27), and 36.4% (4/11) of type O, A, B, and AB patients, respectively. Type AB patients tended to develop GTN compared with other blood type patients ( P = .093). In ABO type of CHMs, GTN occurrence was not significantly different as it was 16.4% (10/64), 16.0% (8/50), and 22.2% (4/18) for types O, A, and B, respectively ( P = .854). According to the ABO incompatibility between patients and molar tissues, GTN occurred in 19.1% (18/94) of the compatible cases and 11.4% (4/35) of the incompatible cases; the occurrence was not significantly different ( P = .223). Conclusion: Patients with type AB tended to develop GTN. However, ABO compatibility between patients and molar tissues had no relationship with GTN occurrence. Abstract : Blood type AB was associated with gestational trophoblastic neoplasia (GTN) development from complete hydatidiform mole. However, ABO compatibility between patients and molar tissues had no relationship with GTN occurrence. Another GTN development mechanism would exist rather than immune rejection.